Hydrothermal Synthesis and Up‐conversion Luminescence of Ho3+/Yb3+ Co‐doped PbTiO3. Issue 18 (10th October 2019) - Xiao, Zhen; Zhang, Jiawei; Zhu, Jing; Xu, Hui; Wang, Huanping; Xu, Shiqing; Xia, Yang
Abstract : Ho 3+ /Yb 3+ co‐doped PbTiO3 nanocrystals with different content of dopant were successfully prepared via a facile hydrothermal method. The purity, morphology, element distribution, chemical state and up‐conversion (UC) photoluminescence (PL) of PbTiO3 nanocrystals affected by Ho 3+ dopant are investigated systematically. X‐ray diffraction (XRD) results illustrate that PbTiO3 samples with the doping Ho 3+ concentration ranging from 0 to 5 mol‐% are perovskite structure. The doping Ho 3+ ions have no change on the crystal structure of perovskite PbTiO3 . Owing to the non‐equivalent substitution of Ho 3+ to Ti 4+ in PbTiO3, the particle size of Ho 3+ /Yb 3+ co‐doped PbTiO3 samples is decreased as well as the particle agglomeration is detected. Moreover, Ho and Yb ions have uniform distributions in the PbTiO3 nanoparticles as the presence of Ho 3+ and Yb 3+ cations. The up‐conversion spectra demonstrate that Ho/Yb co‐doped PbTiO3 samples have up‐conversion emissions centered at 550 nm, 660 nm and 755 nm, corresponding to the transitions of 5 F4 ( 5 S2 )→ 5 I8, 5 F5 → 5 I8 and 5 S2 ( 5 F4 )→ 5 I7 of Ho 3+ ions. Additionally, the effect of temperature on the UC PL property of Ho 3+ /Yb 3+ co‐doped PbTiO3 system is further investigated. The sensitivity and the trend of Ho 3+ /Yb 3+ co‐doped PbTiO3 samples in temperature from 298 k to 493K are calculated on the basis of fluorescence intensity ratio (FIR) method. Ho 3+ /Yb 3+ co‐doped PbTiO3 nanocrystals are verified the high potential in the optical temperature sensing. Abstract :